Geometrically Constrained Polymerization of Styrene Over Heterogeneous Catalyst Layer in Silica Nanotube Reactors. Issue 4 (8th January 2020) - Han, Joong Jin; Lee, Sang Bok; Choi, Kyu Yong
Abstract : Styrene has been polymerized to syndiotactic polystyrene (sPS) over a layer of heterogeneous Cp*Ti(OCH3 )3 /MAO catalyst immobilized onto the surfaces of silica nanotube reactor (SNTR) arrays of 60–200 nm in diameter. The polymer produced in the SNTR arrays has been found to have the molecular weights much larger than the polymers synthesized by a liquid slurry polymerization over silica‐supported catalysts. A dynamic reactor model that consists of diffusion and reaction terms has been derived and solved to quantify the kinetics of styrene polymerization in a single nanotube reactor. The two‐site kinetic model applied to the silica nanotube reactor model shows that the experimentally observed high polymer molecular weight can be fitted if the chain transfer rate constants for monomer and β‐hydride elimination are reduced significantly. The simulation results suggest that the presence of dense crystalline sPS nanofibrils filling the nanotubes constrain the molecular movements of polymer chain ends in the proximity of catalyst sites to limit the chain transfer reactions. POLYM. ENG. SCI., 60:700–709, 2020. © 2020 Society of Plastics Engineers